2012
DOI: 10.1186/1472-6920-12-77
|View full text |Cite
|
Sign up to set email alerts
|

Quality of discharge summaries prepared by first year internal medicine residents

Abstract: BackgroundPatients are particularly susceptible to medical error during transitions from inpatient to outpatient care. We evaluated discharge summaries produced by incoming postgraduate year 1 (PGY-1) internal medicine residents for their completeness, accuracy, and relevance to family physicians.MethodsConsecutive discharge summaries prepared by PGY-1 residents for patients discharged from internal medicine wards were retrospectively evaluated by two independent reviewers for presence and accuracy of essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Because these skills must be learned, young doctors often perceive the writing of DS as a difficult task. Additionally, the lack of systematic teaching often leads to an initially unstructured, inefficient and occasionally incorrect 'learningby-doing' [10,33,69]. Instead, educational training programs, the use of checklists and other structured approaches, as well as audit and feedback, are helpful.…”
Section: General Communication Aspectsmentioning
confidence: 97%
“…Because these skills must be learned, young doctors often perceive the writing of DS as a difficult task. Additionally, the lack of systematic teaching often leads to an initially unstructured, inefficient and occasionally incorrect 'learningby-doing' [10,33,69]. Instead, educational training programs, the use of checklists and other structured approaches, as well as audit and feedback, are helpful.…”
Section: General Communication Aspectsmentioning
confidence: 97%
“…In most hospitals, interns are responsible for completing the majority of discharge summaries but who have received little or no prior training or experience in this task . Not surprisingly, studies have shown that discharge summaries prepared by interns contain more errors and lack clarity compared with those completed by more experienced registrars and consultants …”
Section: Summary Of Discharge Summary Scoresmentioning
confidence: 99%
“…Discharge summaries are a prime example. Research has identified several flaws with current discharge summaries; outpatient practitioners are dissatisfied with the quality [1], and medication reconciliation errors may lead to readmission [2]. Although there have been many efforts to improve authorship of discharge summaries [3-10], little is known about the attitudes of the primary authors of these documents at academic institutions, namely interns, residents, and physician assistants (PAs).…”
Section: Introductionmentioning
confidence: 99%